2011
DOI: 10.1007/s10157-011-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal complications of Castleman’s disease: report of two cases and analysis of 75 cases

Abstract: Biopsy-proven renal complications of Castleman's disease (CD) are rare and current knowledge is largely based on sporadic case reports. We reported two more cases, both of which were multicentric CD with hyaline-vascular pathological pattern and presented with chronic renal failure. Case 1 was multicentric CD with renal mesangial proliferative glomerulonephritis complications, and case 2 was multicentric CD with membranoproliferative glomerulonephritis-like complications. Although both were eventually administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Castleman disease has sometimes been reported to have renal complications. The analysis of renal histology in 75 cases of Castleman disease revealed that a large number of patients had renal amyloidosis (26 cases, 35%), and a small subset had FSGS (5 cases, 7%) [13]. The causal relationship between FSGS and Castleman disease was also unknown, but IL-6 and VEGF, which may play a pathophysiological role in CSP and/or Castleman disease, might contribute to renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Castleman disease has sometimes been reported to have renal complications. The analysis of renal histology in 75 cases of Castleman disease revealed that a large number of patients had renal amyloidosis (26 cases, 35%), and a small subset had FSGS (5 cases, 7%) [13]. The causal relationship between FSGS and Castleman disease was also unknown, but IL-6 and VEGF, which may play a pathophysiological role in CSP and/or Castleman disease, might contribute to renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Between 11 per cent and 30 per cent of patients with POEMS syndrome have multicentric CD, most commonly the HHV-8-positive variant [ 7 ]. Contrary to the HV variant, the PC subtype often shows a clinically aggressive and relapsing course [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 54% of multisystemic Castleman disease, mostly in plasma cell or mixed cellular type, are associated with nephropathy, defined as haematuria, proteinuria or renal insufficiency 11–14. The two main histological patterns are thrombotic microangiopathy (60%) and amyloidosis (20%) 15 16.…”
Section: Discussionmentioning
confidence: 99%